Individualized surgical treatment of giant tuberculum sellae meningioma: Unilateral subfrontal approach vs. endoscopic transsphenoidal approach - Li, Yang; Zhang, Chao; Su, Jun; Qin, Chaoying; Wang, Xiangyu; Li, Yue; Liu, Qing (Frontiers in Surgery, 2022)
OBJECTIVE Giant tuberculum sellae meningiomas (TSMs) are deeply located in the suprasellar region and extensively compressed or encased the surrounding neurovascular structures, making gross total resection (GTR) without postoperative visual impairment challenging. The authors presented individualized unilateral subfrontal approach and endoscopic transsphenoidal approach (ETSA) in a series of patients and elaborated on their advantages and indications in resecting giant TSMs. METHODS Thirty-eight patients with giant TSMs operated by a single surgeon between March 2012 to November 2021 were retrospectively reviewed. Patients underwent unilateral subfrontal approach and ETSA according to preoperative imaging characteristics. Patient characteristics, surgical details, preoperative symptoms, and neurological outcomes were collected and analysed. RESULTS In 31 patients operated with the unilateral subfrontal approach, total resection (Simpson grade I or II) was achieved in 27 patients (87.0%), while 6 patients (85.7%) achieved GTR in other 7 patients using ETSA. The postoperative visual improvement was maintained in 22 (81.5%) and 5 patients (83.3%). Recurrence or progression was only observed in 2 (7.4%) patients operated with the unilateral subfrontal approach. There was no mortality in our series. CONCLUSIONS Preoperative imaging and visual function are important for surgical approach selection. Maximum tumour resection and optic nerve protection can be achieved concurrently by taking advantage of these surgical approaches. The cerebral artery protection strategies and individualized surgical techniques provide great utility in improving a patient’s quality of life.